Improving emergency surgical care for patients with right iliac fossa pain at a regional scale: A quality improvement study using the Supported Champions implementation strategy. (September 2018) - Feinberg, Joshua; Flynn, Lorna; Woodward, Matthew; Pennell, Christopher; Higham, Helen; Morgan, Lauren; Holman, Lance; Tully, Patrick; McCulloch, Peter
Abstract: Introduction: Methods to improve clinical systems safety suffer from significant difficulties in implementation and scaling up. We used an upscaling implementation strategy entitled Supported Champions in a quality and safety improvement programme for emergency surgery at regional level, focusing on patients with right iliac fossa pain. Methods: A before-after study was conducted across four acute NHS Trusts: A 6 month intervention phase was preceded and followed by 3 months of data collection. An established Human Factors intervention was led at each Trust by a small group of staff selected as Champions. Champions received training in teamwork and systems improvement and were supported by Human Factors experts. The primary improvement aim was to expedite surgery for patients with sepsis, using Royal College of Surgeons emergency surgery guidelines as the measure. Additional outcomes studied included length of inpatient stay and 30-day readmission rates. Results: Breaches of RCS urgency guidelines decreased markedly from 13.7% of operated patients pre-intervention to 3.5% post-intervention (p = 0.000). Mean time from booking to incision decreased in three of the four sites, whilst median length of stay increased in 3 of 4. Overall 30-day readmission rate remained stable (7.84% pre-intervention versus 7.31% post-intervention, p = 0.959). Discussion: The Supported Champions model allowed all surgical teams to reduce delay for septic patients by more than 50%, using distinct Quality Improvement strategies to address local issues. Improvement was implemented in 4 diverse settings with a quarter of the level of expert input previously used in a single hospital. Highlights: Quality improvement plus Human Factors techniques improves treatment of suspected appendicitis. Implementing patient safety interventions at larger scales is recognised as difficult. Training respected clinical team members as "Supported Champions" allowed effective up-scaling. Inappropriately delayed surgery for septic patients was reduced 4-fold by the intervention.